Higher Education as an Agent of Religious Moderation: An Analysis of Lecturers' and Students' Perceptions of Nationalistic Insight - Lubis, Putri Handayani; Sari, Nopita; Syah, Firman; Abdullah, Faisal; Sabani, Tria Asri Nur (AT-TURATS, 2024)
Islamic education plays an important role in shaping moderate understanding and attitudes in diversity. Various parties must participate in efforts to create social harmony and peace, so it is important to optimize religious moderation among Muslims. Islamic education plays an important role in shaping understanding and moderate attitudes towards religion. Through quantitative methods, this paper describes the perceptions of students and lecturers towards religious moderation in national insight. Researchers have set four indicators of understanding religious moderation as a reference in obtaining and analyzing data accurately, as follows: 1) having a national commitment, 2) not disturbing others and always respecting other religious opinions, 3) not causing violence both verbal and non-verbal. 4) always appreciating the diversity of local culture. These four indicators have been used to measure or analyze the level of understanding of students and lecturers in the Islamic Education Study Program, IAIN Pontianak about the concept of religious moderation. It can be assumed that the level of understanding of students and lecturers can affect their attitudes and behavior in practicing religious teachings. Therefore, Islamic Religious Education and Character Education can maintain the pillars of moderate character building, emphasizing aspects of tolerance, local wisdom, non-violence, and commitment to the nation, not the other way around, exclusive Islam that even tends to be extreme. This paper contributes to the model of academic-religious development based on religious moderation in higher education. This is important to prevent extremism by strengthening religious practices based on the essence of religious teachings.Pendidikan Islam berperan penting dalam membentuk membentuk pemahaman dan sikap moderat dalam beragam. Berbagai pihak harus berpartisipasi dalam upaya menciptakan harmoni dan perdamaian sosial, sehingga penting untuk mengoptimalkan moderasi beragama di kalangan umat Islam. Pendidikan Islam memainkan peran penting dalam membentuk pemahaman dan sikap moderat terhadap agama. Melalui metode kuantitaif, tulisan ini memaparkan terkait persepsi mahaiswa dan dosen terhadap moderasi beragama dalam wawasan kebangsaan. Peneliti telah menetapkan empat indikator tentang pemahaman moderasi beragama sebagai acuan dalam memperoleh dan menganalisis data secara akurat, sebagai berikut: 1) memiliki komitmen kebangsaan, 2) tidak mengusik orang lain dan senantiasa menghargai pendapat agama lainnya, 3) tidak menimbulkan kekerasan baik yang bersifat verbal maupun non verbal. 4) senantiasa menghargai kebinekaragaman budaya lokal. Keempat indikator tersebut telah digunakan untuk menakar atau menganalisis tingkat pemahaman mahasiswa dan dosen di Program Studi Pendidikan Agama Islam, IAIN Pontianak tentang konsep moderasi beragama. Hal ini dapat diasumsikan bahwa tingkat pemahaman mahasiswa dan dosen dapat memengaruhi sikap dan prilakunya dalam mempraktikkan ajaran agama. Oleh karena itu Pendidikan Agama Islam dan Pendidikan Karakter dapat mempertahankan pilar pembentukan karakter moderat, menekankan aspek toleransi, kearifan lokal, anti kekerasan, dan komitmen terhadap bangsa, bukan sebaliknya, Islam yang eksklusif bahkan cenderung ekstrim. Tulisan ini berkontribusi pada model pengembangan akademik- keagamaan berbasis moderasi beragama di perguruan tinggi. Hal ini penting untuk mencegah ekstremisme dengan memperkuat praktik keagamaan berdasarkan esensi ajaran agama.